Constructing project business around professional identity: business model strategizing of architectural firms - Bos -de Vos, Marina; Lauche, Kristina; Volker, Leentje (A+BE | Architecture and the Built Environment, 2018)
Creative professional service firms experience difficulties in establishing healthy and sustainable business models, as they must reconcile the often competing value systems upon which the models are based. They continuously negotiate between professional values and beliefs and the firm’s commercial goals, resulting in struggles between identity and strategy. Adopting a work lens, this study investigates the reciprocal tensions between identity and strategy in 17 business model design workshops with members of architectural firms. Observational data show that practitioners collaboratively construct their business models around professional values, thereby strengthening organizational identity, but constraining innovation in their business models. The research contributes to the body of literature on business model design processes by articulating how professional aspects of identity enable and constrain practitioners in shaping and being shaped by their strategic actions and decisions.